Dzielmy sie doświadczeniemPerioperative myocardial infarction in women without changes in coronary vessels who have undergone elective aortic bioprosthesis implantation - Goździk, Anna; Pelczar, Marek; Skalik, Robert; Obremska, Marta; Goździk, Waldemar (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Perioperative myocardial infarction in patients after aortic valve replacement is a rare, but very important, life-threatening complication. Case report: A 64-year-old women with significant aortic valve insufficiency was qualified for elective aortic valve replacement. On the second day after the procedure the patient had perioperative myocardial infarction of inferior and anterolateral wall of the left ventricle, causing cardiogenic shock. The infarction was confirmed with ECG and USG examination, as well as by elevated serum markers of infarction (TnI, CKMB). Surprisingly, coronarography revealed no occlusion of any coronary vessels. The patient was intensively monitored and treated for many days afterwards. After reaching stability of the circulatory and respiratory system she was transferred to the rehabilitation unit. Conclusion: Aortic valve replacement might be, although very rarely, complicated by perioperative myocardial infarction, even though there was no evidence for occlusion of the coronary vessels before the procedure. There are a few possible underlying causes responsible for the complication, including transient occlusion of the coronary ostia by embolic material (air, calcium) or incorrect reperfusion or sudden coronary spasm of the coronary arteries.